2021
DOI: 10.1002/cpdd.909
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Abuse Potential in Adult Smokers of a Novel Oral Tobacco Product Relative to Combustible Cigarettes and Nicotine Polacrilex Gum

Abstract: Novel noncombustible tobacco products offer adult smokers (ASs) alternatives to combustible cigarettes lower on the continuum of risk; however, the abuse potential of such products has not been well studied. The objective of this study was to evaluate the abuse potential of 2 chewable tobacco‐derived nicotine containing products, VERVE Chews Blue Mint (test 1) and Green Mint (test 2), in ASs compared with own‐brand cigarettes (CIGS) and nicotine polacrilex gum (GUM) using subjective measures and nicotine pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…On the contrary, the test products complement and may motivate adult smokers who are interested in continuing to use tobacco products to switch away from cigarettes to a less harmful alternative, although not risk free (because they contain nicotine). The evidence indicates this might be possible because, in a previous pharmacokinetic study, the chews test products demonstrated significantly higher nicotine delivery than the 2‐mg Nicorette gum (GlaxoSmithKline, London, England), with similar scores of satisfaction and the willingness to use the product again 5 . Completely switching to oral products like the test products presents a unique harm reduction opportunity for those adult smokers who are unable or unwilling to quit using tobacco products 6‐8 .…”
Section: Dual Use Of Own‐brand Cigarette and Test Products Exclusiv...mentioning
confidence: 97%
See 1 more Smart Citation
“…On the contrary, the test products complement and may motivate adult smokers who are interested in continuing to use tobacco products to switch away from cigarettes to a less harmful alternative, although not risk free (because they contain nicotine). The evidence indicates this might be possible because, in a previous pharmacokinetic study, the chews test products demonstrated significantly higher nicotine delivery than the 2‐mg Nicorette gum (GlaxoSmithKline, London, England), with similar scores of satisfaction and the willingness to use the product again 5 . Completely switching to oral products like the test products presents a unique harm reduction opportunity for those adult smokers who are unable or unwilling to quit using tobacco products 6‐8 .…”
Section: Dual Use Of Own‐brand Cigarette and Test Products Exclusiv...mentioning
confidence: 97%
“…The evidence indicates this might be possible because, in a previous pharmacokinetic study, the chews test products demonstrated significantly higher nicotine delivery 2) 0 (0.0) 0 (0.0) 0 (0.0) 7 (3.3) than the 2-mg Nicorette gum (GlaxoSmithKline, London, England), with similar scores of satisfaction and the willingness to use the product again. 5 Completely switching to oral products like the test products presents a unique harm reduction opportunity for those adult smokers who are unable or unwilling to quit using tobacco products. [6][7][8] Adult smokeless tobacco users, who are accustomed to using oral tobacco products-particularly dual users of smokeless tobacco and combustible cigarettes-may similarly experience reductions in harm by switching completely to the test products.…”
mentioning
confidence: 99%
“…Studies with newer ENDS have shown that those products can generate nicotine yields comparable to, and sometimes exceeding, the nicotine yield from one tobacco cigarette (1.76–2.20 mg) 57–59. Industry-funded studies on novel ONPs suggest that those products deliver nicotine as quickly and to a similar extent as existing smokeless products 60 61…”
Section: Addictiveness and Appeal Of Ends Htps And Onpsmentioning
confidence: 99%